2021
DOI: 10.3390/nu13072287
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hypertriglyceridemia in Patients with COVID-19 Receiving Parenteral Nutrition

Abstract: Hypertriglyceridemia is a metabolic complication associated with parenteral nutrition (PN). It is unknown if patients with acute respiratory distress syndrome (ARDS) secondary to COVID-19 are more at risk. Our aim was to describe the incidence, risk factors and clinical impact of hypertriglyceridemia in critically ill patients with ARDS-COVID-19 receiving PN. We designed a cohort study of patients with ARDS-COVID-19 infection that required admission to critical care units and nutritional support with PN. Indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Two methods, field mass spectrometry and enzymatic determination, are worth exploring: field mass spectrometry is a promising recent technology for measuring electrolyte concentrations in biological fluids [ 164 , 165 ]; its measurement of the sodium concentration based on specific enzyme (β-galactosidase) activation by sodium ions has been applied in certain clinical conditions, e.g., isolation laboratories for emerging infectious diseases [ 26 , 166 , 167 ]. The Supplementary Material Section S1 provides further information about conditions causing hyperlipidemia [ 153 , 154 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 ].…”
Section: Management Of Pseudohyponatremia—future Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two methods, field mass spectrometry and enzymatic determination, are worth exploring: field mass spectrometry is a promising recent technology for measuring electrolyte concentrations in biological fluids [ 164 , 165 ]; its measurement of the sodium concentration based on specific enzyme (β-galactosidase) activation by sodium ions has been applied in certain clinical conditions, e.g., isolation laboratories for emerging infectious diseases [ 26 , 166 , 167 ]. The Supplementary Material Section S1 provides further information about conditions causing hyperlipidemia [ 153 , 154 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 ].…”
Section: Management Of Pseudohyponatremia—future Developmentsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Section S1-Clinical conditions causing increased serum solid content [ 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 ].…”
mentioning
confidence: 99%
“…Thirty-four papers were reviewed after screening, which reported the incidence of hyperlipidemia in COVID-19 patients ( Table 2 ). 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 The incidence of hyperlipidemia ranged from 0.30% to 81.82% in COVID-19 patients among different studies. Potential reasons for the variations could be: 1) Regional factors led to the difference in baseline lipids levels; 2) The definition of hyperlipidemia varied in different studies.…”
Section: The Correlation Between Hyperlipidemia and Covid-19mentioning
confidence: 99%
“…A recent meta-analysis of 18 trials that compared enteral nutrition with parenteral nutrition regardless of timing found no difference in mortality but enteral nutrition was associated with fewer infectious complications and shorter ICU length of stay [74]. Obese patients might be at higher risk of hypertriglyceridemia with parenteral nutrition [75]. Nevertheless, parenteral nutrition could be considered in obese critically ill patients after the first 1 week in the ICU if nutritional targets are not met, particularly in patients who are malnourished.…”
Section: Timing and Route Of Nutritionmentioning
confidence: 99%